Gaya Penyampaian Presenter Program Acara “Tonight Show” Dalam Menarik Minat Penonton - Mochammad Sinung Restendy; Mishbahu Rahmah; Reza Muh Edy Putra Perdana; Ziadatul Fauziah Aryati (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2021)
Each television station presents various programs to attract public interest. No exception with Net TV. This television station presents a Talk show program entitled